Proactive vs. Reactive Aggression Within Two Modified Versions of the Taylor Aggression Paradigm - Boccadoro, Sara; Wagels, Lisa; Henn, Alina Theresa; Hüpen, Philippa; Graben, Lia; Raine, Adrian; Neuner, Irene (Frontiers in Behavioral Neuroscience, 2021)
The Taylor Aggression Paradigm (TAP) has been widely used to measure reactive aggression following provocation during competitive interactions. Besides being reactive, aggression can be goal-directed (proactive aggression). Our study presents a novel paradigm to investigate proactive aggression during competitive interactions. Sixty-seven healthy participants competed in two modified versions of the TAP against an ostensible opponent while skin conductance responses (SCRs) were recorded. During the proactive TAP (pTAP), only the participant could interfere with the ostensible opponent’s performance by blurring the screen. In the reactive TAP (rTAP), the opponent repeatedly provoked the participant by blurring the screen of the participant, impeding their chance to win. In both versions, the blurriness levels chosen by the participant served as a measure of aggression (unprovoked in the pTAP and provoked in the rTAP). In the pTAP, trial-by-trial mixed model analyses revealed higher aggression with higher self-reported selfishness. SCRs decreased with increasing proactive aggression. An interaction effect between gender and proactive aggression for the SCRs revealed increased SCRs at higher aggression levels in females, but lower SCRs at higher aggression levels in males. In the rTAP, SCRs were not associated with reactive aggression but aggression increased with increasing provocation and especially after losing against the opponent when provoked. While males showed higher aggression levels than females when unprovoked, reactive aggression increased more strongly in females with higher provocation. Mean levels of aggression in both tasks showed a high positive correlation. Our results highlight that, despite being intercorrelated and both motivated by selfishness, proactive and reactive aggression are differentially influenced by gender and physiological arousal. Proactive aggression is related to lower physiological arousal, especially in males, with females showing the opposite association. Reactive aggressive behavior is a result of individual responses to provocation, to which females seem to be more sensitive.